Modeling the pelvic suctorial region of Eumicrotremus orbis - Dawe, Ian (Friday Harbor Labs, 2011)
The rocky intertidal zone is a stressful environment inhabited by many organisms with specialized adaptations. One adaptation seen in several families of fish is to use a pelvic suctorial organ to attach to the substrate. This suction mechanism has been detailed in numerous fishes, but there is yet work to be done with how these structures are organized internally. My goal was to produce a three-dimensional model that could readily interact current knowledge of sucker disk morphology, development, and function. I used the software Amira to generate a 3-D model of the elements comprising the suctorial region of Eumicrotremus orbis. This model is easily manipulated and can be reproduced and studied to determine the function of each element. Comparisons with models of different stages of this species as well as models of other species will help us begin answering the question of how such an adaptation originated.
Keywords: Sucker fish, 3-d model, PSO, sucker disk, Cyclopteridae, intertidal zone adaptations